2012
DOI: 10.1039/c1cc14301h
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and light triggering of peptide networks under partial thermodynamic control

Abstract: The kinetics of novel dynamic libraries that operate via reversible replication is described. In these systems, selective product formation is governed by peptides autocatalytic efficiency and by differences in their unfolding stability. We suggest ways to significantly alter the network behavior by chemical inputs (templates) or physical triggers (light).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
47
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 29 publications
(15 reference statements)
3
47
0
1
Order By: Relevance
“…As predicted by the stability value (score = 1.9; Figure 1), and measured earlier, [23] T 2c can serve as a template for R 2 formation. The new network wiring due to addition of the external template changed significantly the competition profile.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…As predicted by the stability value (score = 1.9; Figure 1), and measured earlier, [23] T 2c can serve as a template for R 2 formation. The new network wiring due to addition of the external template changed significantly the competition profile.…”
mentioning
confidence: 98%
“…Thus, in the context of a molecular network, the replicators' thioester bonds facilitate peptide formationdecomposition and direct domain exchange between replicators. [23,33] [a] Ar = 4-acetamidobenzoate, Z =-SCH2CO, K' = Lys-Ar, SR = 2-mercaptoethane sulfonate. À1 ] calculated by summing the values of the three pairwise cross-strand g'8$e13 interactions in each coiled-coil trimer (DDG for Ala$Ala interaction = 0).…”
mentioning
confidence: 99%
“…The durability of thioester bonds in neutral aqueous solutions and their reactivity in thiol-thioester exchange reactions make them a relevant choice for performing dynamic chemistry in water. [10][11][12][13][14][15] Particularly interesting is the possibility of utilizing such transformations for exchanging domains between different protein molecules, owing to sequence mutations or in response to chemical and physical changes.Self-organization of molecular networks has been extensively studied by scientists interested in systems chemistry. [16,17] When studying protein-based networks, it was demonstrated that the network connectivity and overall topology can be dictated by the sequence-specific information embedded in coiled-coil architectures, [18][19][20] and that careful design of the interhelical recognition interface can be used to affect the network in a predictable manner.…”
mentioning
confidence: 99%
“…[16,17] When studying protein-based networks, it was demonstrated that the network connectivity and overall topology can be dictated by the sequence-specific information embedded in coiled-coil architectures, [18][19][20] and that careful design of the interhelical recognition interface can be used to affect the network in a predictable manner. [14,20,21] It is suggested here that the adaptive behavior of such networks, namely their rewiring in response to external triggers, can be greatly expanded if the coiled-coil proteins are formed within dynamic networks in which domain exchange readily takes place. Towards this end, we utilize coiled-coil protein analogues that contain thioester bonds within their sequences.…”
mentioning
confidence: 99%
See 1 more Smart Citation